The implementation of inclusive education in South African private schools: perceptions of parents - Sandler, Genevieve Ann (My University, 2017)
This study aimed to explore parents’ perceptions on inclusive education in private South African schools with the focus on two inclusive practices: bridging classes and classroom facilitators. The sample for this study consisted of 10 parents from two private schools in the northern suburbs of Johannesburg. A semi-structured in-depth interview schedule was devised to examine parents’ perceptions on the support and inclusive practices offered within their schools. The results indicated that majority of parents found bridging classes to be more beneficial than classroom facilitators in assisting children experiencing barriers to learning. Furthermore, results demonstrated that the quality of teaching ultimately influences the success of inclusive education within the school.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Education (Educational Psychology) in the faculty of Humanities, University of the Witwatersrand, Johannesburg, 2016
Keywords: Inclusive education--South Africa; Special education schools--South Africa; Mainstreaming in education--South Africa